Incisional hernia: preliminary observations at a new institute - Huda, Farhanul; Kumar, Abhijit (International Surgery Journal, 2017)
Background: Ventral hernia develops when an area of the abdominal wall weakens and develops a tear or hole. It may develop as a defect at birth, resulting from incomplete closure of a part of the abdominal wall, or develop where an incision was made during an abdominal surgery, occurring when the incision doesn’t heal properly. Incisional hernia is typically observed within the first 5 years after the surgical incision is made, but may develop long afterwards.1 This study was undertaken to review the history and clinical presentations in patients with incisional hernia, and subsequent treatment. Methods: In the present study, the first 20 cases of incisional hernia admitted to this institute for elective herniorrhaphy were studied. History of the previous surgery was obtained and the findings noted. Treatment carried out was included in the study. Results: Out of 20 cases, 12 were female (60%). Mean age of the patient was 41.9±11.9 years. Lower segment Caesarian section was the commonest preceding surgery (7 out of 12 females; 58.33%). Exploratory laparotomy accounted for 5 out of 8 cases amongst males (62.5%). Commonest site of the hernia was infraumbilical (n=9; 45%). Average size of the defect was 6.2 cm x 5.6 cm. 13 patients underwent surgery. Laparoscopic ventral hernia repair was the most common modality used (10 out of 13; 76.9%). Conclusions: Incisional hernia is more common in females, and gynaecological operations are most common cause and most common site is infraumbilical.